Variable-coupled distributed resource allocations for multi-agent system with limited admissible interaction - Luan, Linhua; Qin, Sitian (ISA transactions, 2025)
Variable-coupled distributed resource allocations (VCDRAs) involve optimizing resource distribution among interconnected entities, reflecting the complex correlation in practical systems. Based on the consensus technology, this paper proposes a novel distributed optimization algorithm to address the VCDRA in scenarios where agents are confronted with admissible interaction ranges and external disturbances. Admissible interaction refers to agents only transmitting information within a specified range due to limited communication capabilities or resource availability. The proposed distributed optimization algorithm improves existing interaction mechanisms, reducing computational demands and unifying the communication schemes of the multi-agent system, thereby avoiding additional information exchange. Theoretically, it is proven that the algorithm can get the optimal solution of VCDRA with an exponential rate. Compared to existing algorithms for suppressing external disturbances, the robustness of the proposed distributed optimization algorithm no longer relies on the upper bound of external disturbances, allowing it to remain effective even in the presence of unbounded disturbances. Finally, smart grids and wireless communications applications demonstrate the convergence and robustness of the developed distributed optimization algorithm, further proving its superiority in practical applications. •Address an extended version of past discussions on distributed resource allocations.•Design a new interaction mechanism for admissible interaction of multi-agent systems.•Maintain the effectiveness of the algorithm under general external disturbances.•Simulations in smart grids and wireless systems confirm our theoretical advancements.